2016
DOI: 10.1177/1847980416663674
|View full text |Cite
|
Sign up to set email alerts
|

Control of morphologies and properties of zinc oxide nanorod arrays by slightly adjusting their seed layers

Abstract: A simple method for controllable growth of zinc oxide nanorod arrays by adjusting preparation conditions of their seed layers is studied. Mole ratio of zinc acetate to diethanol amine, concentration of the two chemicals in the solution, and addition of polyethylene glycol in the solution are identified as three key parameters that have a great influence on microstructure of the seed layers. Surface roughness and uniformity in thickness of the seed layer are found as main factors that determine the nanorod arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The XRD spectrum of the Ni–Cu 2 O catalyst confirms the presence of the ITO substrate and the electrodeposited films of Cu 2 O and Ni on the electrode surface as expected (Figure ). The positions of the peaks match the values previously reported for these three components. ,, …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The XRD spectrum of the Ni–Cu 2 O catalyst confirms the presence of the ITO substrate and the electrodeposited films of Cu 2 O and Ni on the electrode surface as expected (Figure ). The positions of the peaks match the values previously reported for these three components. ,, …”
Section: Resultssupporting
confidence: 88%
“…The positions of the peaks match the values previously reported for these three components. 20,22,23 We next analyzed the morphology of Cu This morphology contains a fairly uniform mixture of Cu 2 O and Ni components, and this even distribution with many bimetallic sites may explain why this surface structure leads to optimal OER electrocatalysis. Previous studies with OER catalysts have shown that bimetallic active sites often lead to lower OER overpotentials and outperform their monometallic counterparts.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Subsequently, the(Zn) on the surface of the substrate would oxidize and form ZnO nanorods on the substrate. In the meantime, the oxidation process resulted in the lateral growth of the ZnO core during the attachment of (Zn) atom on the ZnO nuclei core [23]. The growth process of the ZnO NRs is presented in fig.…”
Section: Preparation Of the Zno Nrsmentioning
confidence: 99%
“…Among the (ID) nanostructures, ZnO nanorods (NRs) and nanotubes (NTs) have been widely studied because of their easy formation and device applications [17,18]. Recently different synthesis methods have been devised for ZnO nanostructures such as vapor transport process [19,20], spray pyrolysis [21,22], thermal decomposition [23], chemical bath deposition(CBD) and hydrothermal synthesis [24,25], sol-gel processing [26], direct precipitation and co-precipitation [27][28][29]. Among these methods, vapor deposition (PVD) and chemical vapor deposition (CVD) have been developed to synthesize ZnO nanoparticles into complex structures such as flower-like and web-like agglomerates.…”
mentioning
confidence: 99%
“…11 The development of ZnO films is very attractive for these applications, as the synthesis process can modify their structure and morphology. Within the methods of nanorods synthesis, we can find carbothermal evaporation, 12 seed-layer-assisted solvothermal method, 13 hydrothermal method, 14 and chemical bath deposition. 15 When using the chemical bath deposition process, the substrate is first covered by a thin seed layer of the material to be deposited.…”
Section: Introductionmentioning
confidence: 99%